3 in 1 Super Laundry Machine / Nursyahirah Ismail - Ismail, Nursyahirah (2020)
Supermatic Ltd. manufacture and sells industrial and home cleaning system. We are among leading firms in Malaysia for manufacturing such systems. Our products include Single tank ultrasonic cleaners, Multistage Aqueous ultrasonic cleaner, Multistage vapour degreaser, Oil Skimmers etc. the company is preparing to launch a new product “3 in 1 Supper Laundry Machine” for industrial and home clothes cleaning solutions. Latest technology trends in the consumer washing market incline heavily on Top and front Loading Fully Automatic washing machine with Fuzzy Logic being the sought-after upmarket technology. The lower end of the market is dominated by Semi-Automatic washing machine. Ventless FastDry Technology in washing machine has not been marketed heavily in MALAYSIA market and still to gain space in the consumers consciousness. Our marketing priorities include emphasis on a new cost-effective technology, building brand awareness among customers, targeting specific segment in consumer and business markets, generating sales and breaking even by the end of second year. The company operated in accordance to the environmental regulations. Our capabilities of technical expertise and design the efficient assembly procedures not only contribute to the cost control but also enable us tto react quickly to the market trends and technology advances. For the product’s introduction, we will uses push strategy aimed at channel members offering consumers a technically superior product for the hassle free and cost effective cleaning experience.